Assessment of intercultural communicative competence in FL education: A survey on EFL teachers' perception and practice in China. (2nd April 2016) - Gu, Xiaole
ABSTRACT: The intercultural approach to language teaching, intercultural communicative language teaching, has emerged in response to the limitations of communicative language teaching. As a result, the ultimate goal of foreign language (FL) education is being shifted from communicative competence to intercultural communicative competence (ICC). In China, this calls for an understanding of the status quo of ICC assessment in FL. The aim of the present study, which is a part of a nation-wide survey, is to investigate the opinions and attitudes of teachers of English as a Foreign Language (EFL) in China on assessment of ICC and to gauge how and to what extent these beliefs are reflected in their classroom implementation. Data were collected from 1170 Chinese university EFL teachers by means of a questionnaire. The analysis reveals that, despite a willingness to assess ICC, the EFL teachers lack a clear conception of ICC. This leads to confusion about what should be assessed and how to assess it, and to deficiencies in their attempts to measure students' ICC in the classroom. Possible reasons for the deficiencies are explored and solutions proposed. The findings from this empirical study have implications for intercultural language teaching in China.